2020
DOI: 10.21037/atm-20-3021
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative mannitol intensive use may avoid the early complication of cerebral venous sinus stenting

Abstract: Background: Cerebral venous sinus (CVS) stenting has been widely applied for correcting CVS stenosis.However, there are still some potential complications. The purpose of this study is to investigate the impact of perioperative management on avoiding complications of CVS stenting.Methods: Patients confirmed as CVS stenosis were enrolled from January 2014 through November 2019. All CVS stenosis were corrected by stenting when the trans-stenotic mean pressure gradient (MPG) was up to or over 8 mmHg. Patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…7,35,36 Moreover, our previous study demonstrated that hemorrhage usually occurred in the brain region contralateral to the side of the stent due to transient pressure differences between the two sides that leads to the contralateral perforating vein being pulled and injured. 15 In the present study, 4 patients suffered bleeding events in the control subgroup. The bleeding events included a hemorrhage in right parietal lobe, subdural hemorrhages in the right pare, and intracranial hemorrhage in the preoperative infarcted lesion.…”
Section: Headache and Intracranial Hemorrhage Post-stentingmentioning
confidence: 42%
See 2 more Smart Citations
“…7,35,36 Moreover, our previous study demonstrated that hemorrhage usually occurred in the brain region contralateral to the side of the stent due to transient pressure differences between the two sides that leads to the contralateral perforating vein being pulled and injured. 15 In the present study, 4 patients suffered bleeding events in the control subgroup. The bleeding events included a hemorrhage in right parietal lobe, subdural hemorrhages in the right pare, and intracranial hemorrhage in the preoperative infarcted lesion.…”
Section: Headache and Intracranial Hemorrhage Post-stentingmentioning
confidence: 42%
“…This can result in a friable venous wall that is prone to damage and hemorrhage from endovascular maneuvers 7,35,36 . Moreover, our previous study demonstrated that hemorrhage usually occurred in the brain region contralateral to the side of the stent due to transient pressure differences between the two sides that leads to the contralateral perforating vein being pulled and injured 15 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to prescreen for bony compression in IJVS before stenting, as the high proportion of bony compressions in IJVS (around 40%) may prevent stent inflation 5,8,20 . In addition, early identification and management of rare major complications, such as acute subdural hematoma, cerebellar hemorrhage, acute obstructive hydrocephalus, and subarachnoid hemorrhage, are crucial to achieving a favorable clinical outcome 22,34 . However, the pathophysiology behind these complications is not fully understood, and several studies have discussed their characteristics and potential consequences for surgery and medication 22,29,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other studies that demonstrated that stenting is an effective method for CVSS-induced severe intracranial hypertension correction [ 9 , 18 ]. Although the MPG decreased poststenting, cerebral venous blood flow was restored, and the ICP was corrected immediately poststent management, which is still important for long-term favorable outcomes, and adequate treatment strategies are urgently needed [ 11 , 19 , 20 ].…”
Section: Discussionmentioning
confidence: 99%